The perception of audit rotation within the independent auditors’ view - Quevedo, Mirella Conti (2014)
The audit rotation in Brazil was initiated by the Central Bank of Brazil in response to scandals that have occurred and had put at risk the image of audit firms. Subsequently, the rotation was adopted by the Brazilian Securities Commission, encompassing the publicly-traded companies listed on the stock exchange. Turnover has become a controversial subject, as influences, somehow, in the auditors' relationship with their customers as well as the entire market for audit firms, questioning, this way, its effectiveness. Considering these facts, the aim of this study was to verify with the independent auditors' perception under the audit rotation seeking to understand whether they are favorable or not to this procedure. Thus, this study evaluated the perception of 64 independent auditors of 6 different audit firms, through the survey approach with open and closed questions. The mainly results found that: 91% of the respondents are in favor of the audit rotation; 58% of the auditors believe that the rotation could inhibit the accounting scandals; 56% believe that the costs involved in the rotation turnover outweighs the gains; 76% believe that the accumulated knowledge generates addiction to work; 48% believe that auditors approach the client if there is no rotation. On the other hand, 64 % say that there is a loss of efficiency in auditing with the implementation of rotation and that 74 % of audited companies have not joined the CAE with intent to extend the period of 5 to 10 years of the same auditing firm. The findings of this study when compared to the opinion of public accountancy bodies in relation to the rotation, reveal contradictions. While 91 % of the auditors surveyed advocate the rotation should occur by the company rotation or by rotation of the independent auditor, the CFC and IBRACON are not favorable to rotation. Moreover, CVM provides the rotation for audit firms and the Central Bank for professionals with managerial positions.